A novel 4-(1,3,4-thiadiazole-2-ylthio)pyrimidine derivative inhibits cell proliferation by suppressing the MEK/ERK signaling pathway in colorectal cancer - Li Weiwei; Yang Zhifu; Ding Likun; Wang Ying; Zhao Xian; Chu Jian Jie; Ji Qing; Yao Minna; Wang Jingwen (Acta Pharmaceutica)
Colorectal cancer (CRC) is one of the most common types of malignant cancers worldwide. Although molecularly targeted therapies have significantly improved treatment outcomes, most of these target inhibitors are resistant. Novel inhibitors as potential anticancer drug candidates are still needed to be discovered. Therefore, in the present study, we synthesized a novel 4-(1,3,4-thiadiazole-2-ylthio)pyrimidine derivative (compound 4) using fragment- and structure-based techniques and then investigated the anticancer effect and underlying mechanism of anti-CRC. The results revealed that compound 4 significantly inhibited HCT116 cell proliferation with IC50 values of 8.04 ± 0.94 µmol L–1 after 48 h and 5.52 ± 0.42 µmol L–1 after 72 h, respectively. Compound 4 also inhibited colony formation, migration, and invasion of HCT116 cells in a dose-dependent manner, as well as inducing cell apoptosis and arresting the cell cycle in the G2/M phase. In addition, compound 4 was able to inhibit the activation of the MEK/ERK signaling in HCT116 cells. And compound 4 yielded the same effects as the MEK inhibitor U0126 on cell apoptosis and MEK/ERK-related proteins. These findings suggested that compound 4 inhi bited cell proliferation and growth, and induced cell apoptosis, indicating its use as a novel and potent anticancer agent against CRC via the MEK/ERK signaling pathway.